Natural selection by pollinators on floral attractive and defensive traits did not translate into selection via fruits in common milkweed - García, Yedra; Dow, Benjamin; Vézina, Lucie; Parachnowitsch, Amy (Journal of Pollination Ecology, 2024)
Considering both pollinator and herbivore pressures on plant reproductive and defensive traits is key to understanding patterns of selection for plants. However, phenotypic selection studies connecting floral traits and plant defenses with pollinator activity and herbivore damage remain rare. We used the common milkweed, Asclepias syriaca (Apocynaceae), to study phenotypic selection on attractive and defensive traits, and nectar rewards. We measured herbivore (leaf damage) and pollinator activity (pollinia movement) and quantified selection via female (pollinia insertions and fruit number) and male fitness (pollinia removals). We found selection to increase plant and inflorescence size and to decrease floral size (i.e. petal width) via female fitness. We also detected selection to increase floral but not leaf latex. The lack of selection on leaf latex was congruent with the low herbivory observed, however we also did not observe florivory in the population that would explain the advantage of more floral latex. Interestingly, we found selection on attractive traits differed via pollinia insertions and fruits initiated, suggesting that something other than pollinators was driving selection via fruit production. In contrast to female fitness, we did not find selection on any trait through male fitness, suggesting no sexual conflicting selection, at least through these proxies. Our findings reinforce the importance of the direct assessment of pollinator pressures in phenotypic selection studies before assuming pollinators as drivers of floral evolution by natural selection. Further work in southern populations closer to the centre of the species range, where herbivory and plant defense investment are higher, may help elucidate selection on attractive and defensive traits.